Fluoroscopy-induced chronic radiation dermatitis masquerading as morphea: A diagnostic pitfall - Meenakshi Batrani; Asha Kubba; Joseph Sundharam (Wolters Kluwer Medknow Publications, 2018)
Chronic radiodermatitis is a rare complication of fluoroscopy-guided procedures. The diagnosis of fluoroscopy-induced chronic radiation dermatitis is challenging because of its rarity, late insidious onset, and close clinicopathological resemblance to morphea. We report two cases of fluoroscopy-induced chronic radiodermatitis following cardiac procedures to highlight the clinicopathological features. The diagnosis relies on recognizing the characteristic clinical presentation of well-demarcated, rectangular- or square-shaped indurated plaque with depigmentation, telangiectasia, and ulceration located on the scapula, back, or axilla; supported by the histological identification of radiation fibroblasts in a sclerotic dermis.